2021
DOI: 10.21203/rs.3.rs-902649/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An adjuvanted subunit SARS-CoV-2 spike protein vaccine provides protection against Covid-19 infection and transmission

Abstract: Recombinant protein approaches offer major promise for safe and effective vaccine prevention of SARS-CoV-2 infection. We developed a recombinant spike protein vaccine (called NARUVAX-C19) and characterized its ability when formulated with a nanoemulsion adjuvant to induce anti-spike antibody and T-cell responses and provide protection including against viral transmission in rodent. In mice, NARUVAX-C19 vaccine administered intramuscularly twice at 21-day interval elicited balanced Th1/Th2 humoral and T-cell re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…Nevertheless, the results were highly consistent between the 4 cats in total and the 2 males and 2 females within each group, with statistical differences seen when the adjuvanted vaccine groups were compared to saline controls and/or spike ECD alone immunized animals. Furthermore, the immunogenicity and protective e cacy seen in these juvenile cats of the NARUVAX C-19 vaccine formulation with SWE adjuvant were consistent with the ndings previously obtained for the same vaccine in Syrian hamsters [22]. Another important limitation is the lack of data on long-term protection, on virus transmission and on protection against challenge with the Delta virus variant, as only cross-neutralising antibody data against Delta variant was able to be collected in this study.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Nevertheless, the results were highly consistent between the 4 cats in total and the 2 males and 2 females within each group, with statistical differences seen when the adjuvanted vaccine groups were compared to saline controls and/or spike ECD alone immunized animals. Furthermore, the immunogenicity and protective e cacy seen in these juvenile cats of the NARUVAX C-19 vaccine formulation with SWE adjuvant were consistent with the ndings previously obtained for the same vaccine in Syrian hamsters [22]. Another important limitation is the lack of data on long-term protection, on virus transmission and on protection against challenge with the Delta virus variant, as only cross-neutralising antibody data against Delta variant was able to be collected in this study.…”
Section: Discussionsupporting
confidence: 78%
“…This spike protein ECD antigen has been previously been shown to be immunogenic, protective, and safe in mice and ferrets in an Australian-developed vaccine called COVAX-19/SpikoGen [30] that has successfully passed phase III clinical trials and in October 2021 received emergency use authorization from the Iranian FDA [24]. This spike protein ECD formulated with an SWE adjuvant (NARUVAX-C19 vaccine) provided complete protection of Syrian hamsters against SARS-CoV-2 infection and prevented transmission to naïve animals placed in the same cage as the challenged animals [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the spike protein vaccine with Sepivac SWE ™ , a nanoemulsion oil (SWE) adjuvant, provided better protection to the challenged animals compared to the RBD vaccine using the same adjuvant [65]. Besides, other adjuvants, such as Advax-SM, were also found to be effective for protection against SARS-CoV-2 [66].…”
Section: Vaccinementioning
confidence: 99%